Duration reproduction with sensory feedback delay: differential involvement of perception and action time - Ganzenmüller, Stephanie; Shi, Zhuanghua; Mueller, Hermann J. (Frontiers in Integrative Neuroscience, 2012)
Previous research has shown that voluntary action can attract subsequent, delayed feedback events towards the action, and adaptation to the sensorimotor delay can even reverse motor-sensory temporal-order judgments. However, whether and how sensorimotor delay affects duration reproduction is still unclear. To investigate this, we injected an onset- or offset-delay to the sensory feedback signal from a duration reproduction task. We compared duration reproductions within (visual, auditory) modality and across audiovisual modalities with feedback signal onset- and offset-delay manipulations. We found that the reproduced duration was lengthened in both visual and auditory feedback signal onset-delay conditions. The lengthening effect was evident immediately, on the first trial with the onset delay. However, when the onset of the feedback signal was prior to the action, the lengthening effect was diminished. In contrast, a shortening effect was found with feedback signal offset-delay, though the effect was weaker and manifested only in the auditory offset-delay condition. These findings indicate that participants tend to mix the onset of action and the feedback signal more when the feedback is delayed, and they heavily rely on motor-stop signals for the duration reproduction. Furthermore, auditory duration was overestimated compared to visual duration in crossmodal feedback conditions, and the overestimation of auditory duration (or the underestimation of visual duration) was independent of the delay manipulation.